PSA density lower cutoff value as a tool to exclude pathologic upstaging in initially diagnosed unilateral prostate cancer: impact on hemiablative focal therapy - Höfner, Thomas; Pfitzenmaier, Jesco; Alrabadi, Adel Farah; Pahernik, Sascha; Hadaschik, Boris; Wagener, Nina; Djakovic, Nenad; Hohenfellner, Markus (World journal of urology, 2012)
Purpose: To investigate prostate-specific antigen density as a predictor for pathologic upstaging in patients initially thought to have unilateral prostate cancer. Methods: We analyzed 438 patients with unilateral prostate cancer in prostate biopsy samples that were treated with radical prostatectomy. Bilateral or extracapsular growth in the final surgical specimens was defined as upstaging. Using Kaplan-Meier curves and a multivariate Cox proportional hazard model, we evaluated the oncologic effect of pathologic upstaging on biochemical recurrence-free survival. Prostate-specific antigen density was evaluated as a diagnostic tool to predict upstaging using ROC-curve analysis. Results: Of the patients, 30.8% had bilateral prostate cancer or extracapsular extension in the surgical specimen. Prostate-specific antigen density was a diagnostic predictor for pathologic upstaging in patients initially thought to have unilateral prostate cancer (AUC 0.62, P < 0.001). Using a lower cutoff value of PSA density <0.056 ng/ml/cm3, upstaging could be excluded in patients with a sensitivity of >98%. Conclusions: A considerable amount of patients that are initially diagnosed with unilateral prostate cancer on biopsy are underdiagnosed and are upstaged in the radical prostatectomy specimen. In general, AUC of PSA density is too low to use PSA density as diagnostic tool to predict pathologic upstaging in all patients. Nonetheless, PSA density could be used for hemiablative focal therapy decision making using a lower cutoff value of <0.056 ng/ml/cm3.